THE REPRESENTATION OF FEMINISM IN ADRIENNE RICH'S SELECTED POEMS - Andi Febriana Tamrin (UIN Alauddin Makassar, 2016)
This study is aimed to reveal the feminism idea in Rich's selected poems, a woman author in the mid of 20th century and in Second World War. The feminist theory is the main theory used in analysing the data. Biographical and social approach is used in conducting this study. Those approaches are very helpful in helping to understand the ideas of feminism in Rich's selected poems. Descriptive qualitative and bibliographical are the methods that applied in this study. The result shows that the women in Rich poems did try their best to fight for their rights to oppose the culture and patriarchal society in their time. This can be seen from the analysing of the ideas of the behaviour of women in the poems.